Trastorno de ansiedad y su repercusión en el estado emocional de una niña de 10 años de edad del cantón Pangua - Serrano Falcón, Mariela Elizabeth (2021)
The present case study aims to analyze how anxiety influences the emotional state in a 10-year-old girl from Pangua Canton, on the other hand, it is worth mentioning that after analyzing the girl's medical history, which was carried out using different techniques and tools such as the interview, observation and psychometric tests, an anxiety problem could be verified by applying the Hamilton anxiety test, which reflected the intensity or severity as mild, which determined the diagnosis concerned, complementing even with the Family test, in which affective ambivalence with members of the family system was evidenced. At the same time, the situation presented by the girl was analyzed and once all the results had been verified, it was carried out through Cognitive Behavioral Therapy, in which it facilitated us to achieve results such as the modification of behaviors, cognitive distortions, balance and control of emotions, for a better development of the patient in her daily life.